Therapeutic potential of regulatory T cells for stem cell regulation: Insights from Treg-mediated enhancement of limbal stem cell functions - Fei Fang; Tingxi A; Junzhao Chen; Shiding Li; Tianyi Zhou; Liangbo Chen; Yao Fu; Chunyi Shao (iScience)
Summary: Regulatory T cells (Tregs) play a key role in immunomodulation and tissue regeneration. Limbal stem cells (LSCs) maintain corneal epithelial homeostasis, and LSC deficiency (LSCD) leads to visual impairment. Current LSCD treatments face donor shortages and graft rejection risks. The present study explored Tregs’ therapeutic potential for LSCD in a mouse model of graded LSCD and further explored the direct effect of Tregs on LSCs function by in vitro coculturing human-derived cells. Subconjunctival Tregs injection effectively treated mild and moderate LSCD in mouse models. Coculturing human LSCs with human Tregs promoted LSCs migration, proliferation, and stemness maintenance. Furthermore, amphiregulin (AREG), secreted by Tregs, was crucial to their therapeutic effects, as AREG−/− Tregs resulted in diminished efficacy on LSCD mice compared to wild-type Tregs. These findings highlight Tregs as a promising treatment for LSCD, enhancing LSC function partially via AREG production.